Les mécanismes d'incitations fiscales à l'investissement des entreprises étrangères en France et au Gabon - Engone, Kénaelle Cyndie (Université de Limoges, 2019)
L’attractivité territoriale des Etats se trouve au centre des préoccupations tant au niveau national qu’international. Les mesures fiscales dérogatoires destinées à attirer des investissements étrangers s’avèrent nombreuses et complexes, en raison non seulement de l’influence internationale, mais également des hésitations et de l’accumulation des règles nationales. Au Gabon et en France, les incitations fiscales d’attraction territoriale ont été instruites dans des domaines d’activités clés de l’économie. Elles participent ainsi à l’industrialisation de ces pays. Cependant, au-delà de l’industrialisation, ces mesures dérogatoires visent à développer certaines zones du territoire, et surtout à lutter contre le chômage. Néanmoins, loin de toujours parvenir aux résultats escomptés, ces mesures finissent parfois, au fil des années et des modifications successives à se complexifier, les rendant illisibles. The territorial attractiveness of states is at the center of national and international. Derogatory tax measures designed to attract foreign investments are numerous and complex, not only because international influence, but also hesitations and the accumulation of national rules. In Gabon and France, territorial attraction tax incentives have been educated in key activity areas of the economy. They thus participate industrialization of these countries.However, beyond industrialization, these derogations aim to develop certain areas of the territory, and especially to combat unemployment. Nevertheless, far from always achieving the expected results, these measures end up sometimes, over the years and successive modifications to become more complex, making them unreadable.
Keywords: Aides d’Etat; Attractivité (géographie); Competitiveness; Compétitivité; Emploi; Employment; Fiscalité; Gabon; Impôt; Incitations fiscales; Industrialisation; Investissements; Investments; State aids; Tax incentives; Taxe

Essays on Economics of Litigation : an Application to Investor-State Disputes - Vu, Duy (Université Côte d'Azur, 2019)
International investment treaties often allow the foreign investor to sue the host country before international arbitration in case of breaches of treaty provisions. The number of investor-state disputes is growing so rapidly that some countries expressed their discomfort with the current international investment law regime. The first chapter gives readers a comprehensive view on the effectiveness and spillover effect of international investment arbitration. Based on a vast interdisciplinary literature, we reexamine recent criticisms and identify the root of the crisis faced by international arbitration. We conclude that it is possible for countries to adapt the current regime of international law to new situations without wholesale exit. The second chapter investigates the early settlement of investor-state disputes. Drawing on the rich economic literature and a new dataset related to treaty-based disputes, we find that the host state's experience, the case prospect, the nature of the regulatory measures, the identity of investors and Dutch investment treaties have significant impacts on the probability of early settlement. The third chapter focuses on an institutional dimension of arbitration: the effectiveness of ICSID in solving disputes. The time to resolution and the quality of the final judgment which is measured by the requirement of follow-on proceedings are used as performance indicators. We highlight how arbitrators' biographical and professional characteristics can impact the ICSID effectiveness. Les traités internationaux d'investissement permettent souvent à l'investisseur étranger de poursuivre le pays d'accueil devant un tribunal d’arbitrage international en cas de violation des dispositions du traité. Le nombre de différends entre investisseurs et États augmente si rapidement que certains pays expriment leur malaise à l'égard du régime actuel du droit international de l'investissement. Le premier chapitre donne aux lecteurs une vue générale sur l'efficacité et les effets de spillover de l'arbitrage international en matière d'investissement. En se basant sur une vaste littérature interdisciplinaire, nous réexaminons les critiques récentes et identifions la cause sous-jacente de la crise relative à l'arbitrage international. Nous concluons qu'il est possible pour les pays d'adapter le régime actuel du droit international à de nouvelles situations plutôt que de le quitter. Le deuxième chapitre étudie le règlement amiable des différends entre investisseurs et États. En nous fondant sur la riche littérature économique et sur une nouvelle base de données de différends relatifs à la violation des traités, nous constatons que l'expérience de l'État hôte, les perspectives du différend, la nature des mesures réglementaires, l'identité des investisseurs et les traités d'investissement néerlandais influencent significativement la probabilité d'un règlement rapide du différend. Le troisième chapitre se concentre sur une dimension institutionnelle de l'arbitrage : l'efficacité du CIRDI dans la résolution des différends. Le délai de résolution et la qualité du jugement final, représentée par la probabilité d'avoir des recours post-sentence, sont utilisés comme indicateurs de l'efficacité. Nous soulignons comment les caractéristiques biographiques et professionnelles des arbitres affectent l'efficacité du CIRDI.
Essais en économie du litige : une application aux différends entre investisseurs et Etats
Keywords: Analyse économique; Arbitrage international; Arbitrage international d'investissement; Centre international pour le réglement des différends relatifs aux investissements; Différends investisseur-Etat; Economic analysis; International Investment Arbitration; Investissements étrangers; Investor-state disputes; Médiation internationale

La sécurité alimentaire à l'épreuve du droit international des investissements - Madeleine, Emily (Université Côte d'Azur, 2019)
Si les investissements internationaux contribuent à la réalisation de la sécurité alimentaire, ils peuvent aussi constituer une menace et une voie d’aggravation. L’étude des interactions entre la sécurité alimentaire et les investissements internationaux révèle l’existence de conflits de normes porteurs de risques alimentaires et met en lumière des déséquilibres normatifs dans le droit international des investissements. Ainsi, la mise en œuvre des droits des investisseurs est susceptible de conduire à l’exclusion de la sécurité alimentaire. A l’inverse, l’affirmation de cette dernière peut générer une altération ou une négation des droits des investisseurs. De sorte que, dans cette situation conflictuelle, les obligations alimentaires de l’État ne pourront pas être satisfaites de manière simultanée avec les obligations énoncées dans les accords d’investissements internationaux. Ces conflits normatifs interviennent comme des alarmes et renseignent d’une part, sur les déséquilibres du pouvoir de règlementation des États et des droits exclusifs des investisseurs, et d’autre part, sur l’asymétrie des droits des victimes d’insécurité alimentaire et des droits des investisseurs. L’insuffisance de prévention renforce les contrariétés de décisions et maintient l’assujettissement des États à des obligations contradictoires. Une fois analysés les conflits de normes et les risques alimentaires qu’ils génèrent, il s’avère que les tentatives de résolution de ces derniers, par le biais des techniques classiques, demeurent souvent inopérantes, rendant compte des limites du système actuel. Pour leur part, les risques, la norme et la responsabilité alimentaire restent parfois non identifiés et ne sont pas appréhendés dans leur globalité. Ces circonstances complexifient la résolution des conflits de normes. Dès lors, la thèse s’attache à démontrer que ces conflits sont susceptibles parfois d’être évités, ou réduits, puis, envisage un traitement dans la résolution de ces derniers en vue de parvenir à une articulation entre les droits des investisseurs étrangers et la protection de l’intérêt public alimentaire de l’État d’accueil de l’investissement.
Keywords: Aide alimentaire; Aliments; Approvisionnement; Conflits de normes; Food security; Foreign investment; International investments; Investissements internationaux; Investissements étrangers; Investments; Norm conflicts; Sécurité alimentaire

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Le régime juridique du financement islamique Moucharaka en investissement immobilier - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Il s'agit de la traduction d'une thèse déjà présente dans référencée sur notre sité
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

Le cadre juridique des investissements internationaux en République démocratique du Congo - Iririra Nganga, Dan (Aix-Marseille Université, 2019)
L’investissement étranger est considéré aujourd’hui comme un facteur clé voire une valeur ajoutée à même de faciliter le développement de l’État d’accueil. Ainsi, l'État congolais mise sur l’amélioration de son arsenal juridique interne dont l’objectif consiste à attirer de nombreux investisseurs et investissements étrangers sur son territoire. Pour ce faire, des réformes tendant à l’amélioration de principaux textes juridiques applicables directement ou indirectement en matière d’admission et de sécurisation des investissements étrangers afin de se conformer aux standards internationaux deviennent une obsession pour cet État, dont la finalité demeure : la valorisation de ses ressources naturelles notamment le cobalt, le germanium et la colombo-tantalite etc. très souvent inexploitées et utile à même de servir à la production des batteries pour les voitures électriques. Il serait donc nécessaire désormais que le contrôle de l’État souverain sur ses ressources naturelles considérées comme des minerais stratégiques soit davantage renforcé et que le contentieux en matière d’investissement soit confié à des entités qui prennent en compte l’intérêt général au détriment des arbitrages sous l’égide des arbitres privés, défendant les intérêts privés. Ainsi, la création d’un Centre international africain de règlement des différends pourrait être profitable notamment en permettant aux experts africains - tant arbitres qu’avocats - d’être plus présents dans le cadre des procédures impliquant leurs États d’origine. Foreign investment is now considered a key factor or even an added value that can facilitate the development of the host country. Thus, the Congolese State is focusing on improving its domestic legal arsenal, the objective of which is to attract many foreign investors and investments to its territory. To this end, reforms aimed at improving the main legal texts directly or indirectly applicable to the admission and security of foreign investments in order to comply with international standards are becoming an obsession for this State, the purpose of which remains: the development of its natural resources, in particular cobalt, germanium and colombo-tantalite etc., which are very often unexploited and useful for the production of batteries for electric cars. It would therefore now be necessary for the sovereign State to strengthen its control over its natural resources considered as strategic minerals and for investment litigation to be entrusted to entities that take into account the general interest to the detriment of arbitrations under the aegis of private arbitrators, defending private interests. Thus, the creation of an African International Dispute Resolution Centre could be beneficial, in particular by allowing African experts - both arbitrators and lawyers - to be more present in proceedings involving their States of origin.
Keywords: Accords bilatéraux; Admission; Bilateral agreements; Congo (République démocratique); Droit; Eclatement; Expropriation; Fair and equitable treatment; Inadequacy of the law; Inadéquation du droit; Incohérence; Inconsistency; Intérêt national; Investissements étrangers; L’obsolescence des règles; Minerais stratégiques; Nationalisation; Obsolescence of rules; Permanent sovereignty; Ressources naturelles; Securisation; Souveraineté permanente; Splitting; Strategic minerals; Sécurisation; Sécurité juridique; Traitement juste et équitable; Transparence; Transparency

Le refinancement d'entreprises en difficulté : contribution à l'optimisation juridique du concept de capital-retournement - Feydel, Romain (Université de Limoges, 2019)
Le refinancement d’entreprises en difficulté est entouré d’une grande part de mystification. Aux yeux du grand public, il s’agit avant tout d’un moyen efficace de faire fortune pour les investisseurs s’y aventurant. Cette activité, connue également sous le nom de capital-retournement, est pourtant le domaine d’exercice exclusif de hauts techniciens de la finance et du droit. Le vaste droit de l’ingénierie financière encadre le refinancement d’entreprises en difficulté. Plongeant son lecteur au coeur de la haute finance d’entreprise, cette thèse démystifie le capital-retournement tout en voulant améliorer sa pratique. Pour cela, l’aspect juridique de la levée des fonds et de leur investissement fait l’objet d’une profonde analyse. À partir de celle-ci et de l’inspiration du droit étranger, de nouveaux outils dédiés à l’optimisation du refinancement d’entreprises en difficulté sont proposés. Cette thèse démontre le rôle prépondérant du droit de l’ingénierie financière dans le sauvetage d’emplois en France.
Keywords: Banking and financial law; Droit bancaire; Droit de l'investissement; Droit financier; Droit privé; Fiscalité; Ingénierie financière; Investment Law; Taxation

La transparencia en el arbitraje internacional y en los tratados bilaterales de inversión - Febles Pozo, Nayiber (Universitat de Girona, 2019)
The thesis's main objective is the analysis of transparency in international arbitration. To this purpose, we start from a broad conception of the notion of transparency and its relevance in the current Bilateral Investment Treaties (BITs) and in the main international arbitration regulations: the ICSID, the ICC, UNCITRAL and its Rules on Transparency in Treaty-based Investor-State Arbitration, followed by a study of the most important issues of the arbitration procedure related to transparency, such as public hearings, the participation of third parties in the procedure (third-party funders and amicus curiae), the appointment of arbitrators and the conflict of interests and, finally, the analysis of transparency in the decisions (arbitral awards). The thesis proposes and bases, among other issues, the need to create an ICSID Court of Appeal and, if not, the most suitable mechanism for the implementation of an International Investment Tribunal
Keywords: Advertising; Arbitrage; Arbitragem; Arbitraje internacional; Arbitration; Bilateral Investment Treaties (BITs); Confidencialidad; Confidencialitat; Confidentiality; Ethical principles; International Arbitration; International Investment Tribunal; Investments; Investor-state arbitration; Preciding; Principios éticos; Principis ètics; Publicidad; Publicitat; Transparencia; Transparency; Transparència

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

La rentabilité de l'investissement dans la responsabilité sociale d'entreprise "RSE" : pourquoi et comment ? - Espinassouze, Aline-Laure (CY Cergy Paris Université, 2018)
Selon le modèle théorique de la « RSE stratégique », la responsabilité sociale des entreprises, définie comme un investissement dans la qualité des relations avec les parties-prenantes stratégiques de l’entreprise, s’intègre dans la logique économique de l’entreprise. Partant de l’hypothèse d’une corrélation universellement positive entre RSE et FI, la question se pose du processus et du contexte par lesquels cette création de valeur s’effectue : si la RSE est un investissement rentable, peut-on expliquer pourquoi et comment ?La base de données Gaïa-Index mise à disposition par l’agence de notation RSE française EthiFinance permet d’étudier cette question sur une population d’entreprises françaises cotées de taille moyenne (N=230) durant la période 2011-2013. Les résultats sont en cohérence avec le consensus théorique et empirique sur la RSE stratégique et montrent que le « facteur humain » est un élément fondamental du processus de création de valeur permettant d’associer performance RSE et performance financière.
Keywords: CSR; Capital humain; Employee turnover; Human capital; Investissements; Investments; Performance; RSE; Strategy; Stratégie; Turnover

Le développement durable dans les traités régionaux africains d'investissement : cas de la CEDEAO et de la SADC - Koula, Bablésson Mardochée Désiré (Université de Bordeaux, 2018)
L’appréhension du tandem développement durable – traité d’investissement a longtemps été perçue sous l’angle de la contradiction. En effet, bien qu’il existe un consensus sur l’importance des investissements en tant que vecteur du développement durable, les seuls instruments internationaux qui leur sont spécifiquement dédiés [les traités d’investissement] font généralement peu, ou pas, cas de cet objectif ; ceux-ci étant conçus dans le seul but d’assurer une protection élevée des investisseurs et leurs investissements. Toutefois, depuis une décennie, on voit émerger au sein des organisations régionales africaines de nouveaux modèles de traités d’investissement dont l’unique but est de promouvoir les investissements qui soutiennent le développement durable. Ce changement de paradigme, qui prône désormais la compatibilité du régime juridique de l’investissement transnational avec les exigences sociales et environnementales, n’est cependant pas sans soulever des interrogations. Parmi celles-ci se pose la question de savoir comment l’engagement en faveur du développement durable est concrètement traduit dans ces traités régionaux. L’interrogation est capitale, surtout lorsqu’on sait les difficultés qui entourent l’analyse du développement durable, concept et objectif à la fois multidimensionnel et évolutif. À cet égard, l’étude des instruments de la CEDEAO et de la SADC témoigne de la prise en compte du développement durable à un double niveau. D’abord, l’adaptation, à travers l’aménagement des clauses traditionnelles des traités d’investissement (PARTIE I). Ensuite, l’innovation, par l’introduction de dispositions jusque-là inexistantes dans la pratique conventionnelle (PARTIE II). The understanding of the tandem of sustainable development and investment treaty has long been seen in terms of contradiction. Indeed, although there is a consensus on the importance of investments as a vehicle for Sustainable Development, the only international instruments specifically dedicated to them [investment treaties] generally pay little or no attention to this objective; they are designed with the sole aim of ensuring high protection for investors and their investments. Over the past decade, however, new models of investment treaties have emerged in African regional organizations with the sole aim of promoting investments that support sustainable development. However, this paradigm shift, which now advocates the compatibility of the legal regime of transnational investment with social and environmental requirements, raises some questions. Among these is the question of how the commitment to sustainable development is concretely reflected in these regional treaties. The issue is crucial, especially when one considers the difficulties surrounding the analysis of Sustainable Development, a concept and objective that is both multidimensional and evolving. In that regard, the study of ECOWAS and SADC instruments reflected the consideration of Sustainable Development at two levels. First, adaptation, through the amendment of the traditional clauses of investment treaties (Part I). Secondly, innovation, through the introduction of provisions which had not previously existed in Treaty practice (Part II).
Keywords: Africa; Afrique; Communauté économique des États de l'Afrique de l'Ouest; Durable; Développement durable; Investissements; Investments; Regional; Southern African Development Community; Sustainable; Traités; Treaties

La protection juridique des investissements directs étrangers dans les pays en développement : l'exemple de l'Afrique de l'Ouest - Fall, Cheikh Lo (Université de Bordeaux, 2018)
Les IDE sont au cœur de la mondialisation et des rapports Economiques Nord-Sud. La question de leur protection et de leur régulation juridique se pose avec acuité. Devant la rareté des autres sources de financement du développement et d’accès à la technologie, l'IDE constitue une source importante pour combler l'insuffisances des ressources internes. raison pour laquelle, les pays d'Afrique de l'ouest se livrent à une concurrence farouche pour les accueillir. Dans la sous région ouest africaine le droit et la réglementation sont utilisés comme des instruments importants pour mesurer l'attractivité et la sécurité juridiques des pays. Le sujet s'interroge, analyse la dimension sécuritaire(traitement et garantie) a t'elle permise une plus grande promotion et d'accueil des IDE?. Notre sujet tentera d'analyser et situer l'effectivité du régime juridique des investissements étrangers au plan interne( codes des investissements, codes miniers et codes pétroliers). Mais aussi au plan externe( Traité bilatéraux d'investissement TBI,conventions sectoriels de protection arbitrage et garantie). Le dernier axe de ce travail de recherche, est le phénomène de la Communautarisation de la protection avec les tentatives d'harmonisation et d'uniformisation des réglementations nationales en Afrique de l'Ouest. Le dernier aspect, c'est l'institutionnalisation à travers les Organisations Economique Internationales (Banque Mondiale et Banque Africaine de développement BAD) du système juridique de protection en Afrique de l'Ouest. "The protection of foreign direct investment in developing countries: the example of West Africa" FDI is at the heart of globalization and north-south economic relations. The question of their protection and legal regulation is acute. Faced with the scarcity of other sources of development finance (development aid) and the difficulties of access to technology, FDI is an important resource for filling the insufficiency of internal resources. This is why African countries in general, and those in West Africa in particular, are competing vigorously to receive foreign capital by providing them with an attractive, secure and non-discriminatory legal and institutional framework. Indeed, in the West African subregion, the law is used by States, but also by subregional integration organizations such as ECOWAS as an important instrument for demonstrating economic attractiveness. Thus, the analysis and measurement of the legal and institutional framework for FDI in West Africa will be discussed. In other words, has the security dimension of the investment (reception, processing, guarantee and settlement of disputes etc.) allowed for greater promotion and reception of investments from these countries?The interest of the subject is multiple. Indeed, at the legal and academic level, it allows to know, analyze and situate the entire legal regime of foreign investment at the internal level (investment code, mining code, oil code). At the external level, there is a multitude of conventions - such as bilateral BIT investment treaties -, accession to the relevant international investment conventions, and of course the increasingly visible and visible role of Community law in through the "communitisation of the law of foreign direct investment". The study of this subject shows the deep gap that exists between theory and practice in the FDI legislation of the countries of this part of Africa. If, upstream, the texts are more or less similar to those of the advanced countries, downstream, the execution of the texts by the public administrations makes mediocre the environment and the practice of the businesses. This theme on the legal protection of investments raises other questions and issues such as: the intervention of more and more actors and the instruments negotiated within them (World Bank, ADB, WTO, OECD, ECOWAS and UEMOA). etc.). There are also new issues related to environmental issues, corporate social responsibility and heritage issues. Finally, the problems posed by new types of investment, particularly PPP public-private partnerships, will be studied. The current nature of the research is striking, as there are several issues related to investment protection in countries such as West Africa. It is about the transfer of technology in a new context, the industrialization by the natural resources, the contribution on the development of the host country and the creation of jobs especially in an international context where Africa became again attractive.
Keywords: Afrique de l'Ouest; FDI; Foreign investment; Ide; Investissements; Investissements étrangers; Investments; Juridique; Protecting; Protection; West africa

Les émanations de l'État à vocation économique dans l'arbitrage des investissements et dans le contentieux de l'O.M.C - Cortesi, Giulio Alvaro (Université Paris 1 ; Università degli Studi di Padova, 2018)
L'idée de cette thèse sur le droit international des investissements concernant les entreprises d'État trouve son origine dans l'impressionnant développement économique de ces dix dernières années. D'une part, ce dernier donne une pertinence considérable à ce thème compte tenu de son actualité. D'autre part, il existe un intérêt considérable pour les problèmes juridiques laissés en suspens par ces entités. Cette thèse commence par un chapitre préliminaire dans lequel la forme juridique de ces institutions est analysée, à la fois avec une évaluation empirique et du point de vue du droit national et international applicable à ces sujets. L'analyse empirique approfondie qui n'a pas encore été réalisée dans les recueils de contributions examinés s'est révélée fondamentale, car certaines des questions juridiques concernant les entreprises d'État ne pourraient vraiment pas être abordées sans une telle approche. Le corps plus juridique de la thèse, consacré uniquement à l'analyse juridique, est composé de trois parties et présente deux principaux pôles d'intérêt : le premier est lié à la compréhension des implications juridiques de ces entités et le second, plus large, vise à comprendre le traitement qui a été réservé à ces organes dans les différends examinés. Ce traitement peut nous renseigner au niveau systémique sur le droit international des investissements, qui a également nécessité une comparaison ciblée avec l'arbitrage commercial et avec le droit commercial international. The idea of a thesis on state enterprises in international investment law finds its roots in their impressive economic development during the last decade, which, on one hand, gives considerable relevance to this theme given its inherent actuality and, on the other hand, there is a considerable interest in the juridical problems that these entities leave open. The thesis consists of a preliminary chapter, were the legal form of these institutions has been analyzed, from both an empirical assessment and the standpoint of national and international law applicable to these subjects. The empirical, in-depth analysis, not yet reached in the collections of examined contributions, turned up as fundamental, because some of the legal issues concerning state enterprises cannot really be tackled without such an approach. The more juridical body of the thesis, devoted only to legal analysis is composed of three parts and has two main poles of interest: the first linked to the understanding of the legal implications of these entities and a second, and, wider one, aimed at understanding what the treatment of these bodies, occurred in the dispute cases examined, can tell us at a systemic level about international investment law, which has required also a targeted comparison with commercial arbitration and international trade law.
Keywords: Contentieux d'investissement; Contentieux fiscal; Contentieux économique; Economic litigation; Entreprises publiques; Finances publiques; Fond souverain; Investment arbitration; State enterprises

La protection internationale des investissements étrangers en Afrique de l'ouest : espace CEDEAO (Communauté Économique des États de l’Afrique de l’Ouest) - Diop, Papa Abdoulaye (Université Côte d'Azur, 2018)
La protection internationale des investissements étrangers dans la Communauté Économique des Etats de l’Afrique de l’Ouest (CEDEAO) suppose d’établir la compétence de celle-ci à assurer une sécurisation des biens des opérateurs économiques ressortissants d’Etats tiers dans son espace. Ainsi, il a été démontré que, par le biais de ses instruments de réalisation de l’intégration régionale, cette organisation communautaire pourrait être amenée à assurer une sécurisation des investissements étrangers. Mais, quoique fusse grande la volonté de la CEDEAO d’assumer une telle fonction, l’analyse démontre qu’elle présente certaines insuffisances qui sont intrinsèquement liées à la différence de nature entre le droit communautaire et le droit conventionnel des investissements. Face à ce constat, il urgeait de trouver d’autres instruments supplétifs, voire complémentaires dans la protection communautaire des investissements étrangers. Ces dits instruments ont été localisés dans le droit international général, tant à travers ses règles substantielles que ses mécanismes procéduraux. Cependant, si la protection que procure le droit de la CEDEAO sur les biens des investisseurs étrangers a été jugée inefficace, celle du droit international, en revanche, semble excessive au point d’être préjudiciable aux Etats hôtes, si tant qu’elle nécessite un nivellement. À l’examen, l’observateur pourrait avoir la sensation qu’il existe un bras de fer entre le droit international et le droit communautaire dans la sécurisation des biens des opérateurs économiques étrangers. Cet observateur constatera ensuite que le droit de la protection des étrangers entre dans une nouvelle ère. En effet, longtemps limitée dans le cadre bilatéral entre Etat d’origine et Etat d’accueil de l’investissement, la problématique de la sécurisation des investissements étrangers a acquis une telle acuité dans la vie économique des entités étatiques qu’elle tend à devenir une affaire de communauté. Il se rendra, enfin, surtout compte que, si le droit conventionnel des investissements a pour visée la protection des étrangers, il peut, à certains égards, constituer un stimulant à la bonne gouvernance. The international protection of foreign Investments within the Economic Community of West African States (ECOWAS) requires establishing the competence of the latter to ensure the security of the property of economic operators who are nationals of third States in its area. Thus, it has been shown that through its instruments for achieving regional integration, this community organization could be led to ensure the security of foreign investments. But, although ECOWAS’s willingness to assume such a function is great, the analysis shows that it has certain shortcomings which are intrinsically linked to the difference in nature between Community law and the Conventional law of investment. In this view, it was urgent to find other supplementary and even complementary instruments in the community protection of foreign investments within the community. These instruments have been localized in General International Law both through its substantive rules as in its procedural mechanics. However, while the protection afforded by ECOWAS law to the properties of foreign investors has been found to be ineffective, that of the international law, on the other hand, seems excessive to the point of being detrimental to host States, as long as it requires leveling. On examination, the observer might have the feeling that there is a tug of war between International law and Community law in securing the assets of foreign economic operators. This observer will then note that the law of the protection of foreigners enters a new era. Indeed, for a long time limited in the bilateral framework between the State of origin and the host States of the investment, the issue of securing foreign investments has acquired such acuity in the economic life of the State entities that it is tends to become a community affair. Finally, i twill be appreciated that, while the purpose of conventional investment law is the protection of foreigners, it may, in some respects, be a stimulus to good governance.
Keywords: Afrique occidentale; Arbitrage commercial international; Arbitrage d'investissement; Bilateral Investments Treaties; CEDEAO; CIRDI; Communauté économique des États de l'Afrique de l'Ouest; Droit international; Droit international des investissements; ICSID; International Investment Law; Investissements étrangers

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

Contrats internationaux en Algérie : applicabilité des conventions fiscales au service de l'investissement - Kaloune, Salah (Aix-Marseille, 2018)
L'Algérie a engagé une politique de libéralisation de son économie et cherche à intégrer l’économie mondiale pour sortir de sa dépendance des hydrocarbures et diversifier son économie. Une politique incitative est mise en place pour accueillir les investissements direct étrangers qui constituent un enjeu majeur pour l’accroissement des échanges, le transfert de technologie, la mise à niveau des sociétés locales et la création d’emploi. D’un autre côté la mise en place d’une économie de marché exige un environnement juridique efficace et stable qui définit clairement les droits et obligations des opérateurs économiques notamment en matière de conclusion de contrats. Le cadre théorique que nous retenons pour répondre à cette question est l’analyse de la place des conventions fiscales dans l’ordre fiscal algérien et sa corrélation avec la politique de promotion des investissements. Les conventions fiscales sont telles réellement au service de l’investissement ? Pour ce faire nous avons mis en exergue tout au long de nos développements l’examen des conventions fiscales à l’épreuve des contrats internationaux permettant d’améliorer la lisibilité et la transparence de la norme fiscale afin de favoriser l’attractivité du territoire
Keywords: Algérie; Attractivity; Attractivité; Attractivité (géographie); Contrats internationaux; Conventions fiscales; Double imposition (traités); FDI; Foreign direct investment; International contracts; Investissement direct étranger; Investissements étrangers; Investments; Permanent establishment; Tax treaties; Établissement stable

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
URI: http://hdl.handle.net/10019.1/103466
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
https://escholarship.mcgill.ca/concern/theses/s1784p10r
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims

الاطار القانوني للاستثمار العربي في الجزائر - عبد الصدوق, حفيظة (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
للاستثمار العربي في الج ا زئر أهمية خاصة لسببين: أحدهما يتعلق بأهمية الاستثمار في حد ذاته لما يلعبه من دور لا يستهان به في التنمية الاقتصادية للدولة، مؤث ا ر على كل جوانب الحياة في المجتمع بما يوفره من تطور اقتصادي وازدهار واستق ا رر، وثانيهما يرتبط باتخاذه وسيلة لتجسيد التعاون العربي المشترك وتحقيق التكامل المنشود منذ عقود، والذي تأكد عدم تحققه الا بالاعتماد على المدخل الإنتاجي من خلال توظيف رؤوس الأموال العربية في الدول العربية. بدافع هذين العاملين وجذبا لرؤوس الأموال العربية وضعت الج ا زئر اطا ا ر قانونيا ا زخ ا ر بالضمانات والامتيا ا زت بعد تحديد مفهوم الاستثمار العربي، هذا الإطار يتألف من الاحكام الاتفاقية السامية على التشريع الوطني الواردة في الاتفاقيات المبرمة بين الج ا زئر والدول العربية بعد المصادقة عليها، ومن احكام التشريع الوطني الذي يعد آلية قانونية تنفذ بها الدولة است ا رتيجياتها. ت ا زمن ذلك مع تهيئة مناخ الاستثمار بصفة عامة من خلال الإصلاحات التي طالت مختلف التشريعات المتعلقة بإقامة الاعمال اولاستثمار في الج ا زئر. جاءت هذه الد ا رسة لتبين معالم هذا الإطار القانوني، مكوناته ومدى تأثيره في رفع مست وى الاستثمار العربي في الج ا زئر كما ونوعا، ضمن مشاريع التكتل الإقليمي والجهوي او المبادلات الثنائية مع الدول العربية.
Keywords: Accords bilatéraux; Algeria; Arab Nationality; Arbitrage; Arbitration; Bilateral Agreements; Blocage; Blocking; Business Establishment; Compensation; Création d'entreprise; Encouragement; Garanties; Guarantees; Investissements; Investment Protection; Investments; Nationalité arabe; Privileges; Privilèges; Protection des investissements

Les obligations internationales de l’Etat d’accueil d’un investissement étranger et leur sanction dans l’ordre juridique international - Edouard, Régis (Université Paris 10, 2017)
L’encadrement, par le droit international, du comportement de l’État hôte d’un investissement étranger n’est concevable que dans la mesure où sa souveraineté est limitée, l’enjeu étant la sanction de l’inobservation, par cet État, de ses obligations. Ces dernières sont issues de la pratique conventionnelle, surtout bilatérale, regroupant des traités qui disposent au fond. L’«internationalisation» du régime juridique de l’investissement n’est pas exclue comme mode de formation d’obligations mais ne se produit qu’à la faveur de dispositions dotées d’un tel effet. La pratique conventionnelle, assez uniforme, a comme principale caractéristique l’articulation de règles limitant le besoin d’interprétation autour de standards qui l’amplifient. Ceci, de même que les interprétations arbitrales, autorise à soupçonner une volonté de « remembrement » du standard minimum international. Si l’attribution d’un comportement à l’État d’accueil ne pose pas de difficulté inédite, l’établissement d’une violation, par cet État, de « ce qui est requis de lui » révèle des singularités de ce domaine. La qualification des circonstances excluant l’illicéité en situation d’urgence peut s’avérer problématique, le risque étant omniprésent d’une méconnaissance, de la part des arbitres, de la logique du droit de la responsabilité. En dehors de ces situations, on peut imaginer des hypothèses dans lesquelles l’illicéité est exclue suite au consentement de l’État d’origine ou de l’investisseur. Le préjudice subi par ce dernier, objet de la réparation intégrale due par l’État responsable, constitue le « préjudice causé par le fait internationalement illicite ». Il est immédiat et direct. L’investisseur, titulaire du droit d’invocation de la responsabilité de l’État hôte, a accès à une réclamation internationale qui éclipse celle de son État de nationalité. La perspective d’un endossement, par ce dernier, de la réclamation de son national accroît l’efficacité des traités d’investissement. For the conduct of a foreign investment’s host State to be governed by international law is only conceivable insofar as its sovereignty is limited, since the issue is the sanction of the failure of that State to fulfill its obligations. The latter results from a mostly bilateral treaty practice embodying treaties which contain material provisions. The “internationalization” of the legal regime of an investment is not excluded as a means to create obligations, but only occurs through provisions with such an effect. The main characteristic to this fairly uniform treaty practice is the development of rules limiting the need for interpretation around a core set of standards amplifying it. This, as well as the arbitral interpretations, may reflect a desire to “consolidate” the international minimum standard. If the attribution of conduct to the host State does not raise any unprecedented issue, the establishment of a violation by that State of “what is required of it” reveals singularities in this field. The characterization of circumstances precluding wrongfulness in an emergency situation may prove problematic, as the risk that arbitrators may ignore the logic of the law of responsibility is omnipresent. Apart from these situations, it is possible to imagine hypotheses in which wrongfulness is precluded due to the consent of the State of origin or the investor. The injury sustained by the latter, which is the subject of full reparation due by the responsible State, constitutes “injury caused by the internationally wrongful act.” It is immediate and direct. The investor, entitled to invoke the responsibility of the host State, has access to an international claim which eclipses that of his State of nationality. The prospect of an espousal by the latter of its national’s claim increases the effectiveness of the investment treaties.
Keywords: Arbitrage transnational; Foreign investment; International responsibility; Investissement étranger; Investissements étrangers (droit international); Investment treaty; Investments; Obligation primaire; Obligations internationales; Primary obligation; Responsabilité internationale; Souveraineté; Sovereignty; Traité d’investissement; Transnational arbitration; État (responsabilité)

Recherche sur la notion d'investisseur protégé par le droit international - Atanasov, Ognyan (Université Paris 1, 2017)
A la différence d'autres catégories de personnes privées, comme par exemple celle des commerçants qui, s'ils peuvent tirer profit des règles internationales mises en place par les États relatives au libre exercice du commerce, n'ont généralement pas la capacité de se prévaloir à titre individuel des droits leur conférant ces règles dans l'ordre international, l'investisseur est devenu aujourd'hui destinataire direct d'un nombre important d'instruments conventionnels, et dispose grâce aux mécanismes de règlement des différends prévus par ces derniers d'un droit d'action individuel à l'encontre des États étrangers. Par le terme « investisseur», les conventions de protection des investissements étrangers désignent aussi bien les individus que les personnes morales. Traditionnellement, en contentieux interétatique, un État ne peut exercer sa protection diplomatique qu'en faveur de ses nationaux, à condition cependant que l'individu ne possède pas en outre la nationalité de l’État destinataire d'une telle réclamation. Le droit conventionnel des investissements a apporté une certaine évolution en la matière. D'une part, de plus en plus de traités étendent leur application non seulement aux nationaux des États contractants, mais également aux individus ayant établi leur résidence sur le territoire de ces derniers. D'autre part, certaines conventions prévoient expressément que lorsqu'un individu-investisseur dispose à la fois de la nationalité de l'un des États contractants d'un traité et de celle d'un autre État contractant, contre lequel il entend adresser une réclamation, c'est la nationalité la plus effective de la personne physique qui doit conditionner la recevabilité de sa demande au niveau international. Concernant le régime de protection des personnes morales, en contentieux de la protection diplomatique la Cour internationale de Justice accorde uniquement à l’État où est constituée la société, le titre pour agir en sa faveur à l'encontre d'un autre État. Cette règle a été très critiquée au motif que souvent l’État d'incorporation d'une société, contrôlée par des ressortissants d'un autre État, n'a pas toujours un intérêt suffisant pour défendre les droits de celle-ci vis-à-vis d'un troisième État auteur d'une mesure préjudiciable pour cette société. L’État réellement intéressé par un recours serait plutôt celui de nationalité des associés de la personne morale lésée. En tenant compte de ce dernier constat, le droit conventionnel des investissements a conféré la capacité aux associés d'une société lésée pour agir en protection des actifs de cette dernière, sans pour autant remettre en cause la qualité à agir de la société pour la protection de ces mêmes biens et avoirs. Lorsque le titulaire d'un investissement est une personne morale, celle-ci n'est alors plus perçue comme un seul investisseur, mais comme une pluralité d'investisseurs potentiels. La société peut être traitée soit comme une personne juridique unique, soit comme une addition des personnalités de tous ses associés, détenant directement ou indirectement son capital, et disposant le cas échéant de nationalités différentes, et donc de titres juridiques multiples leur permettant d'agir à l'encontre de l’État ayant porté atteinte à l'investissement réalisé par une telle personne morale.
Keywords: Clause de déni des bénéfices; Corporate law; Droit des sociétés; Droits des associés; International law; Intérêt social; Investissements étrangers (droit international); Investisseur; Investments; Investors; Nationality; Nationalité; Rights of the associates; Résidence; Société

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Le droit des investissements internationaux vu par la CIJ et le CIRDI - Tanon, Abédjinan M. Sandrine (Université de Bordeaux, 2016)
Le droit des investissements internationaux est largement présenté au travers de la jurisprudence arbitrale, notamment celle du CIRDI. Une telle approche a paru insuffisante. En effet, dans l'examen des questions touchant le droit des investissements internationaux, la jurisprudence de la CIJ et de sa devancière semble être un passage obligé à certains égards. S'agissant de règles primaires, c’est dans la jurisprudence de la Cour qu’ont émergé et pris forme certaines règles substantielles relatives aux investissements internationaux, et dont la désuétude est loin d'être établie par l'avènement du CIRDI. Par ailleurs, le rôle général de la Cour dans le fonctionnement de l'ordre juridique international à travers les règles juridictionnelles, procédurales, d’interprétation ou encore de responsabilité internationale, est indéniable. Or, certaines de ces règles se présentent comme des chapitres incontournables du droit des investissements internationaux. Ce sont là autant de raisons qui ont conduit à entreprendre une étude sur Le droit des investissements internationaux vu par la CIJ et le CIRDI en l’abordant au travers de la question de savoir si les tribunaux CIRDI puisent dans l’héritage de la Cour sur les problématiques juridiques relatives aux investissements internationaux ou s’en départissent. La confrontation des jurisprudences de la Cour et des tribunaux CIRDI a permis de conclure que le droit des investissements internationaux vu par la CIJ n’est que partiellement le droit des investissements internationaux vu par les tribunaux CIRDI. Globalement, sur une problématique donnée, en même temps que certaines solutions retenues par la jurisprudence des tribunaux CIRDI dénotent un emprunt aux règles et principes posés par la Cour, d’autres s’en départissent, qu'il s'agisse des règles primaires en la matière, ou bien des règles secondaires du droit international dans leur déclinaison dans le cadre du droit des investissements internationaux. Parce qu’elle livre, entre autres, une vue d’ensemble de la jurisprudence de la Cour de la Haye en matière d’investissements internationaux – démarche inédite –, la thèse se présente comme une piste pour les arbitres sur le chemin de l’émergence d’une jurisprudence arbitrale cohérente en droit des investissements internationaux.
Keywords: Applicable law; CIJ; CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Consentement; Contrats d'état; Cour internationale de justice; Coutume; Custom; Droit applicable; Droit des investissements internationaux; Equitable treatment; Expropriation; Fair treatment; Foreign investment; Full protection; Full security; ICJ; ICSID; International Investment Law; International responsability; Investissements étrangers; Investments; Minimum standard of treatment; Most favoured nation treatment; National treatment; Pleine protection et sécurité; Protection des actionnaires; Responsabilité internationale; Shareholder protection; Standard minimum de traitement; State contracts; Traitement de la nation la plus favorisée; Traitement juste et équitable; Traitement national

Le cadre fiscal de l'investissement français en Tunisie - Amor, Mehdi (Université Toulouse 1 Capitole, 2016)
Le cadre fiscal de l’investissement français en Tunisie tend à assurer la liberté d’investissement et renforcer l’ouverture de l’économie tunisienne à l’étranger en assurant un traitement non discriminatoire envers les investissements français en Tunisie. Il contient notamment des règles d’incitations fiscales qui couvrent la majorité des secteurs. Toutefois, ce cadre fiscal n’est pas suffisant pour promouvoir l’investissement français en Tunisie.
Keywords: Conditions économiques; Droit fiscal; Investissements; Investissements français; Investissements étrangers; Investments; Tunisie

Effets des institutions sur les investissements directs étrangers dans les pays de l'UEMOA : une approche par le méthode de panel ARDL - Bagaga, Mamoudou (Université Cheikh Anta Diop, 2016)
Dans un monde globalisé et fortement concurrentiel, les économies sont à la recherche permanente de capitaux en vue de renforcer leur tissu industriel, gage d'une croissance soutenue au service du développement et de l'emploi. Dans ce sens, une frange importante de chercheurs et de praticiens s'accordent sur l'importance du cadre institutionnel. Or les pays de l'Union économique et monétaire ouest africain (UEMOA) disposent d'un cadre institutionnel peu performant. Et à cela s'ajoute la faiblesse des flux de capitaux directs étrangers qu'ils enregistrent. Ces capitaux seraient d'ailleurs concentrés dans des secteurs peu productifs. C'est pourquoi, cette thèse se propose d'analyser l'influence de la qualité des institutions dans l'attractivité et l'efficacité des investissements directs étrangers (IDE) des pays de l'UEMOA. A cet effet, nous avons développé un modèle théorique inspiré de Feng & Chen (1997) pour analyser les mécanismes en jeu. Ainsi, dans le but de réduire d'une part, les problèmes d'endogénéité des variables explicatives notamment des variables institutionnelles, et d'autre part, de se conformer aux caractéristiques de notre échantillon et de capter les dynamiques de court terme et de long terme, la méthodologie utilisée pour les estimations des modèles empiriques est celle des modèles de panel Autorégressifs à Retards Echelonnés (ARDL). Avec une prédominance des relations de long terme entre les différentes variables, trois principaux résultats émergent de cette thèse. D'abord, une amélioration de la qualité des institutions (corruption, crises socio-politiques, démocratie, respect de la loi et de l'ordre) a permis d'attirer davantage d'investisseurs privés étrangers. Ensuite, le faible développement des institutions s'est accompagné d'un comportement de recherche de rente accru des dirigeants provoquant une éviction de certains investisseurs locaux par ceux étrangers. Enfin, ces insuffisances institutionnelles dans les pays de l'UEMOA ont atténué les effets d'entraînement sur la croissance économique qu'auraient pu avoir les IDE. Face à ces conclusions, il urge pour chaque pays de l'Union de se pencher sérieusement sur des politiques de réformes de leurs institutions notamment à travers la promotion de la démocratie, tant au niveau national qu'au niveau communautaire. Ces politiques devraient favoriser non seulement l'attractivité des IDE, mais aussi la complémentarité de ces derniers avec les investissements privés locaux.
Keywords: ARDL panel; Croissance économique; Domestic private investment; Economic growth; Foreign direct investment; Investissement direct étranger; Investissement domestique privé; Investments; Modèle de panel ARDL; UEMOA; WEMU

Commerce international et investissements directs étrangers : complémentarité ou substituabilité ? - Tayara, Saeed (Université de Poitiers, 2016)
Ce travail étudie, théoriquement et empiriquement, l'interaction entre le commerce international et l'investissement direct étranger (IDE), interaction qui a été un des principaux canaux de la mondialisation économique et de l'essor des chaînes de valeur mondiales dans la segmentation des activités de production. Les modèles théoriques montrent que le commerce international et les IDE peuvent se développer dans une relation de substituabilité ou de complémentarité. La nature de cette relation peut être la conséquence de facteurs exogènes, déterminants de la spécialisation des pays, ou le résultat de la stratégie endogène des firmes dans l'organisation de leurs activités à l'international. La validation empirique s'appuie sur une adaptation du modèle de gravité, en appliquant les techniques économétrique sur données de panel sur des données bilatérales pour la France au cours de la période de 1993 à 2012. Les estimations mettent en évidence une relation de complémentarité entre le commerce et l'IDE au niveau le plus agrégé. Cependant, une analyse comparative à un niveau plus désagrégé permet de trouver des indices de substituabilité et de complémentarité selon les groupes de pays partenaires.
Keywords: Commerce extérieur; Commerce international; Complementarity; Complémentarité; Données de panel; Entreprise multinationale; Entreprises multinationales; Foreign direct investment; Gravity model.; International Trade; Investissement étranger direct; Investissements étrangers; Modèle de gravité; Modèles économétriques; Multinational firm; Panel data; Substituabilité; Substitutability

A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

Attractivité économique des investissements directs étrangers en zone CEMAC : harmonisation des instruments juridiques aux règles internationales - Memphil Ndi, Evelyne Patience (Université de Nice Sophia-Antipolis, 2015)
Les courants de la mondialisation des marchés, marqués par la libre circulation des capitaux et le phénomène du libre-échange ont favorisé la mise en œuvre de politiques communautaires de relance économique et d’attractivité des territoires. C’est dans cette lancée que des regroupements géographiques à visée économique comme la Communauté Économique et Monétaire de l’Afrique Centrale (CEMAC) sont apparus. Six pays de l’Afrique Centrale dont le Cameroun, le Congo, le Gabon, la Guinée Equatoriale, la République Centrafricaine et le Tchad en sont membres et font l’objet de notre analyse sur l’attractivité économique de l’investissement Direct étranger (IDE) dans cette sous-région. L’IDE est devenu un acteur incontournable du processus de développement, et la zone CEMAC une destination privilégiée pour les investisseurs. Il apparait néanmoins une ambiguïté dans les rapports entre le flux d’IDE, la croissance économique et le développement des pays membres de la CEMAC : le taux sans cesse croissant des flux d’IDE entrants dans la sous-région, n’est malheureusement pas toujours synonyme de croissance économique. Pour comprendre ce paradoxe, l’on procède à une analyse des instruments encadrement de l’IDE dans la sous-région CEMAC. Il en ressort que, pour un rendement optimal de ces dispositifs et la garantie d’une croissance économique à long terme dans ces États, il est nécessaire d’associer les politiques actuelles d’attractivité économique des IDE, à une diversification des domaines économiques exploitables , mais aussi adapter les standards internationaux aux spécificités socioculturelles mais aussi économiques de la sous-région CEMAC. The currents of the globalization of the markets, marked by the free movement of capital and the phenomenon of free trade supported the implementation of Community policies of economic revival and attractivity of the territories. It is in this impetus that geographical regroupings with economic aiming like the Economic community and Monetarist of Central Africa (CEMAC) appeared. Six countries of Central Africa of which Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic and Chad are members and are for it, the object our analysis on the economic attractivity of direct foreign investment (FDI) in this under-area. The FDI became an inevitable actor of the development process, and CEMAC zones, a privileged destination for the investors. It appears nevertheless an ambiguity in the relationship between the flow of FDI, the economic growth and the development of the member countries of the CEMAC : the rate unceasingly crescent of flows of FDI entering the under-area, is unfortunately not always synonymous with economic growth. To understand this paradox, one carries out an analysis of the instruments framing of the IDE under-area CEMAC. This reveals that, for an optimal output of these devices and the warranty of one long-term economic growth in these States, it is necessary to associate the current policies of economic attractivity of the FDI, with a diversification of the exploitable economic domains, but also to adapt the international standards to sociocultural but so economic specificities of under-area CEMAC. The case of the countries of the BRICS can in this respect, being used as illustration for an “other way” of thinking the development.
Keywords: Afrique centrale; Attractivité économique; Communauté Economique et Monétaire de l'Afrique Centrale; Conditions économiques; Economic attractivity; Foreign direct investment; Harmonisation; Harmonization; Investissements directs étrangers; Investissements étrangers

Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
https://ir.unilag.edu.ng/handle/123456789/4079
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
URI: http://webcat.warwick.ac.uk/record=b2766071~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

The Investment Treaty Regime and Public Interest Regulation in Ghana: Perspectives in Constitutionalism and General International Law - Dagbanja, Dominic (University of Auckland, 2015)
There is extensive literature on conflict of legal norms and interests in international investment law. The dominant discourse is on the implications of treaty-based investment protection for sovereign regulatory autonomy. Mainstream scholarship critical of the scope and effect of investment treaties has taken the legal status of these treaties for granted. Little systematic attention has been paid to the capacity of states to make investment treaties and the obligations states can or cannot agree to under those treaties in light of their public interest obligations. Yet, this issue is of fundamental importance for three reasons. First, the case for states’ regulatory autonomy arises out of their primary duty to regulate in the public interest. This duty has its legal justification in national constitutions and international law. Second, treaty obligations are founded on the existence of legal norms necessary for the treaty to come into existence and which define the juridical consequences attached to the conclusion of the treaty. These matters are also determined by national constitutions and international law. Third, the limitations inherent in state-specific defences in international investment disputes settlement compel a proactive rethink of the conclusion of investment treaties and how they are interpreted. The question this thesis assesses with reference to Ghana then is: does a state that is legally required to act both under the terms of its constitution and international law in the public interest have the capacity to conclude investment treaties that expressly prevent or abridge the exercise of its public interest regulatory powers, and how should treaties adopted in breach of these obligations be interpreted? To address this question, three areas of public interest regulation that have featured prominently in investment arbitration serve as case studies: the jurisdiction of municipal courts, environmental protection and development policy. Based on the impact and potential limitations of standards of investment protection on these areas, the thesis argues that some treaties are incompatible with the public interest regulation obligations of Ghana under the Constitution and international law. The core proposition of the thesis is that the legal source and public purpose of the State’s powers prevent it from concluding agreements that directly prohibit public interest regulation or indirectly achieve that effect. Accordingly, the thesis proposes that the express and implied limitations on the duty to regulate in the public interest placed on investment treaty making powers of the State must inform the making of investment treaties and their interpretation. By its approach, this thesis establishes a principled basis for reflection on the limits to the State’s capacity to conclude investment treaties and on how they should be interpreted.
http://hdl.handle.net/2292/28285
Keywords: Ghana; Investment treaty; Investments; Public interest

آليات تهيئة مناخ الإسثمار الأجنبي المباشر في الجزائر - بن طراد, أسماء (Ibn Khaldun University of Tiaret, 2015)
تهدف هذه الدراسة إلى استعراض تجربة الجزائر في مجال جذب الاستثمار الأجنبي المباشر من خلال الإشارة إلى جهودها المبذولة في سبيل تهيئة المناخ الاستثمار لامتلاكها مجموعة من مؤهلات واتخاذها العديد من مزايا التي تأهلها على استقطابه ، إلا أنها مازالت رغم ذلك تصنف ضمن المراتب الأخيرة من طرف الهيئات الدولية نظرا لوجود عدة عوامل تحد في مجملها من تدفق الاستثمارات الأجنبية إليها، لهذا خلصت هذه الدراسة إلى محاولة استعراض مجموعة من الآليات الكفيلة بتهيئة مناخ الاستثمار في الجزائر وجعله يتمتع بالاستقرار والجاذبية على جميع المستويات، وبناء تصور متكامل لعوامل جذب الاستثمار الاجنبي في الجزائر للفترة 1980-2012 ، لمعرفة أثرها على تدفقات الاستثمار الأجنبي المباشر واقتراح معالجات مناسبة لها بما ينعكس بالإيجاب عليها مستقبلا.
Keywords: Algérie; Climat d'investissement; Environnement des affaires; FDI; Foreign direct investment; Investissement direct étranger; Investments

An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

L'investissement : étude juridique - Grundeler, Guillaume (Aix-Marseille Université, 2014)
L'investissement est une notion récente dans la sphère juridique. Voici quelques années, elle n'était encore employée que dans la règlementation relative au contrôle des investissements étrangers. C'est que, si le droit n'ignorait pas l'investissement, il le saisissait presque uniquement à travers d'autres notions, tels l'apport en société ou le mouvement de capital. Depuis lors, le mot a été très largement juridicisé. Pour s'en tenir à deux exemples, on peut ainsi relever que, dans notre ordre interne, l'existence d'un investissement permet une durée contractuelle longue et que, dans l'ordre international, la qualification d'investissement est aujourd'hui une condition de la compétence des tribunaux arbitraux statuant sous l'égide du Cirdi.Cet accès spontané de l'investissement à la juridicité s'est malheureusement accompagné de certaines incohérences. Ainsi, le mot est parfois employé de manière excessivement large, comme en droit des marchés financiers, où il désigne toute opération relative à un instrument financier. De même, en droit des régimes matrimoniaux, ce que la Cour de cassation nomme les « dépenses d'investissement » recouvre en réalité l'ensemble des dépenses immobilières. Parfois, à l'inverse, certaines opérations dont la qualification d'investissement ne fait aucun doute continuent d'être envisagées à travers des notions qui en sont le simple reflet. L'objet de la thèse est donc de rétablir une certaine cohérence dans l'emploi du mot investissement en proposant une définition juridique de la notion et en esquissant certains éléments du régime qui s'y attache.
Keywords: Apport; Arbitrage d'investissement; CIRDI; Capital contribution; Centre international pour le réglement des différends relatifs aux investissements; Civil liability; Contrôle des investissements étrangers; Droits sui generis du producteur de bases de données; Duration of the contract; Durée contractuelle; Foreign investment regulation; Foreign investments; France; Free-Riding; ICSID; Investissements; Investissements étrangers; Investisseur; Investment arbitration; Investments; Investor; Parasitisme; Responsabilité civile; Return on capital; Rémunération; Sui generis right of the producer of a database

Les produits structurés et la protection de l'investisseur - Gomez Richa, Lucia (Université de Genève, 2014)
La présente étude propose une analyse juridique des produits structurés (art. 5 LPCC), qui la conduit à une réflexion plus large quant à la protection de l'investisseur en droit suisse, de lege lata mais également au regard de l'avant-projet de loi sur les services financiers. L'étude met tout d'abord en lumière les incohérences et les insuffisances du système juridique actuel. Elle propose une définition nouvelle des produits structurés assurant une cohérence au système. Avec comme fil conducteur et illustration la complexité des produits structurés, la thèse explique et critique le retard de la réglementation suisse en matière de protection des investisseurs, tant s'agissant de la conception juridique de l'investisseur que de la concrétisation des règles de conduite par l'émetteur et les distributeurs. Elle expose et discute les règles et pratiques existantes visant à répondre à certains des enjeux posés. Enfin, la thèse énonce des propositions d'amélioration à ces règles, en grande partie relayées par l'avant-projet de loi sur les services financiers.
Keywords: Anlage (Investition); Anlagefonds; Derivative Finanzinstrumente; Instruments dérivés (finances); Investisseurs directs; Produits structurés; Produits structurés (finances); Protection; Protection de l'investisseur; Risque financier; Réglementation des marchés financiers; Schweiz; Sociétés d'investissement; Suisse

Venture capital: valor da informação, riscos e instrumentos para sua mitigação - Silva, Fernando César Nimer Moreira da (Universidade de São Paulo, 2014)
Venture capital é espécie de empreendimento que vincula dois agentes econômicos, empreendedor e investidor, visando ao desenvolvimento de uma ideia inovadora para posterior comercialização no mercado. O empreendedor é detentor de conhecimento sobre a ideia e o investidor possui os recursos para desenvolver o projeto. O negócio se diferencia dos demais pelo alto grau de incerteza e risco do empreendimento e requer o uso de tipos contratuais adequados para sua limitação. O projeto se inicia com a etapa de contratação, na qual as partes negociam a divisão de riscos e retorno do negócio, seguindo-se a etapa de monitoramento do desenvolvimento das atividades. Ao final ocorre o desinvestimento, com a saída do investidor e venda do negócio. Do ponto de vista da Economia, utilizamos a Teoria dos Jogos e apresentamos os problemas informacionais, riscos e incertezas do negócio, e os incentivos para organizar a cooperação entre as partes. Do ponto de vista de Finanças, debatemos a decisão de financiamento do negócio e as alternativas para diversificação dos riscos do investimento, isto é, a possibilidade de limitação dos riscos pela adoção de estratégias de contenção, que aumentam o interesse em contratar o negócio. Do ponto de vista do Direito, avaliamos qual a estrutura contratual ideal para organizar esse tipo de empreendimento. Analisamos as principais formas usadas para organização do negócio, em especial as sociedades limitadas e as sociedades anônimas fechadas. Avaliamos o suporte normativo aplicável, com destaque para a possibilidade de limitação dos riscos do projeto pela aplicação das normas de Direito Societário a esses empreendimentos. Os principais riscos aplicáveis são os riscos de contratação do negócio, os riscos de alocação do poder de decisão entre os sócios e os riscos de interrupção prematura do projeto. Devido à natureza e características do negócio de venture capital, concluímos que esse tipo de projeto é mais bem organizado como um contrato plurilateral e que não há tipo contratual ideal para alinhar os interesses. Dos tipos existentes, a sociedade anônima fechada é o mais adequado, mas incapaz de limitar todos os riscos do negócio. A conclusão é confirmada, parcialmente, pelas evidências empíricas apresentadas. Venture capital is a business that links two economic agents, entrepreneur and investor, aiming to develop an innovative idea for future sale on the market. The entrepreneur holds knowledge about the idea and the investor has the resources to develop the project. It is distinguished from others by the high degree of uncertainty and risk of the project and requires the use of appropriate contract types for its restriction. The project begins with the contracting stage, in which the parties negotiate the division of risks and return business, followed by the monitoring of the development of the business activities. At the end occurs the divestment, in which the finished business is sold by the investor. From the point of view of Economics, we use Game Theory to present the informational problems, business risks and uncertainties, and the incentives to organize the cooperation between the parties. From the standpoint of Finance, we discuss the decision to finance the business, and alternatives for risk diversification, that is, the possibility of limiting the risks by adopting containment strategies that may increase the interest in contracting. From the point of view of Law, we evaluate the ideal contractual structure for organizing this kind of project. We analyze the main existing contract types, in particular, the limited liability companies and the closed corporations. We present our concerns about the normative support applicable to that type of business, emphasizing the Corporate Law problems. We evaluate the normative support applicable, emphasizing the possibility of limiting the project risks by applying the Corporate Law rules to such ventures. The main risks are the risks applicable to the contracting phase, the risk of incorrect allocation of decision rights between the partners and the risk of premature termination of the project. Due to the nature and characteristics of the venture capital business, we conclude that this type of design is best organized as a plurilateral agreement and that there is no contract type that can be considered ideal to align the interests. Considering all the existing types, the private corporation contract is the most appropriate form, but also unable to limit all the business risks. The conclusion is partially supported by the empirical evidence presented.
Keywords: Capital de risco; Capital-risque; Closed company; Closed corporation; Contract; Corporate finance; Direito comercial; Game theory; Instruments; Investimentos; Investment fund; Law and economics; Limited liability company; Mercado de capitais; Risk; Risque; Uncertainty; Venture capital

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments

L'émergence du droit international des investissements : contribution des traités bilatéraux d’investissement et de la jurisprudence du CIRDI - Danic, Olivia (Université Paris 10, 2012)
La relation dialectique qui unit les traités bilatéraux d’investissement et la jurisprudence du Centre International de Règlement des Différends relatifs aux Investissements (CIRDI) a fait émerger un droit international des investissements. La rencontre de ces deux dynamiques a permis de dépasser leur caractère a priori isolé et fragmenté, pour aboutir à un véritable système juridique international, doté d’une structure, d’une logique et de principes propres. En effet, rien ne pouvait laisser envisager une telle évolution, le régime de l’investissement international se fondant sur une multitude de traités bilatéraux et sur une instance arbitrale ne faisant qu’héberger des tribunaux éphémères. Les mouvements de va-et-vient qui unissaient ces deux phénomènes ont permis de lui donner des normes quasi-universelles, mais aussi un véritable juge à la compétence extensive et surtout de lui insuffler l’unité, l’efficacité, la cohérence et la complétude, faisant de plus en plus ressembler le droit international des investissements à un véritable ordre juridique qui, même s’il relève du droit international, lui permet également d’évoluer. The relashionship between bilateral investment treaties and the case-law of the International Centre for Settlement of Investment Disputes (ICSID) has led to the emergence of international investment law. It seems surprising, at first, that these two distinct phenomena, being isolated and fragmented, would reach a certain degree of unity so that a real international legal order could appear, with its own structure, reasoning and principles. No one could foresee such an evolution, the regime of international investment being founded on a large number of bilateral treaties and on an international institution which only provides facilities for arbitration of international investment disputes. The unity of the system has been discovered through the back and forth movements between treaties and arbitration which gave rise to international investment law. This system has now almost universal norms, an international judge and satisfies the criteria of unity, efficiency, consistency and completeness, producing a real legal order functioning in accordance with its own logic. There is no doubt that this evolution will influence the course of international law.
Keywords: Arbitrage; Arbitrage (droit); Arbitration; Bilateral Investment Treaties (BITs); CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Droit international; ICSID; International law; Investissements; Investissements étrangers (droit international); Investment; Investments; Jurisprudence; Legal order; Ordre juridique; Traité bilatéral d’investissement

Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
https://repository.up.ac.za/handle/2263/24525
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets

Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

La qualification d'investissement étranger : contribution à la notion juridique d'investissement et à la définition de l'extranéité - Onguene Onana, Dieudonné Edouard; Prujiner, Alain (Université Laval, 2011)
La compétence d'un arbitre chargé d'appliquer le droit international des investissements exige l'existence préalable d'un investissement étranger. Cette étude vise à identifier ce qui constitue un investissement parmi l'ensemble des opérations économiques et financières et à déterminer les conditions auxquelles il doit répondre pour être considéré comme étranger. L'importance de la Convention de Washington explique l'attention particulière portée au Centre international pour le règlement des différends relatifs aux investissements (CIRDI). La diversité des traités bilatéraux et des autres sources normatives dans ce domaine a conduit à proposer une approche fondée sur une dissociation du contrôle sur la base des sources normatives de la compétence arbitrale. Après un exposé introductif sur l'évolution des modes de règlement des différends relatifs à la propriété étrangère et son aboutissement à l'arbitrage international actuel, la première partie de l'étude est consacrée à la définition de la notion juridique d'investissement dans une perspective de qualification par l'arbitre. La seconde partie analyse la seconde exigence pour établir la compétence de l'arbitre, celle d'extranéité de l'investissement, et elle expose les conditions liées à la nationalité de l'investisseur.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Investissements; Investissements étrangers; Investments; Sociétés

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation